Trends Associated with Stillbirth in a Maternity Hospital School in the North Zone of São Paulo: A Cross-Sectional Study - Fonseca, Raissa Magalhães de Mendonça; Garcia, Carolina Laila; Angimahtz, Talita Sampaio; Battaglia, Cindy Fazio; Chalem, Elisa; Sass, Nelson (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate conditions associated with stillbirth (SB), and possible trends related with it, in a maternity hospital school in the North zone of São Paulo.Methods An observational, cross-sectional study conducted at the Hospital Maternidade-escola de Vila Nova Cachoeirinha with 1,139 SBs in the period of 2003 to 2017. Cases of intermediate SB (ISB) (weight between 500 and 999 g) and late SB (LSB) (weight ≥ 1,000 g) were compared. We evaluated clinical data, laboratory tests, and fetal and placental studies. Data were stored in Windows Excel (Microsoft Corp., Redmond, WA, USA) worksheets, according to which graphs and tables were constructed. We used the statistical software SPSS for Windows version 18.0 (SPSS In., Chicago, IL, USA), estimating the prevalence ratio (PR) and odds ratio (OR), considering the 95% confidence interval (95% CI).Results The general SB rate was 11.9%, and the in-hospital SB rate was 2.8%. Pregnant women younger than 16 years of age were more likely to have ISB (OR 0.32, 0.15–0.76), while patients older than 40 years old had a higher chance of LSB (PR 0.85, 0.72–0.99). A total of 25.7% of the general population did not have prenatal care, and 77.1% of the cases presented fetal death at admission. The cases of ISB had a statistically significant association with home birth (OR 0.61, 0.46–0.80). Cesarean section was performed in 16.1% of the subjects, and misoprostol was the most used method for induction. Necropsy and placental study of the fetuses were performed, respectively, in 94.2% and 97.3% of the cases. Associated causes were not identified in 22.1% of the cases, and the main causes identified were amniotic sac infections (27.9%), fetal malformations (12.5%), placental abruption (11.2%), hypertensive syndromes (8.5%), and maternal syphilis (3.9%), the latter with an increasing trend.Conclusion Among the factors associated to SB were: hypertensive syndromes, amniotic sac infections, fetal malformations, placental abruption and syphilis. There was a growing trend in the number of cases of syphilis, which translates an alert. Diagnostic limitations justify indeterminate causes.
Keywords: stillbirth; epidemiology; primary health care; prenatal care; pregnancy high-risk